IMPLEMENTASI PERATURAN BUPATI KUANTAN SINGINGI NOMOR 12 TAHUN 2012 TENTANG PENERTIBAN TERNAK DAN HEWAN PENULAR RABIES DI KABUPATEN KUANTAN SINGINGI TAHUN 2012 – 2013 - Richo Rahgia Syahputra; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research based on abundant natural wealth Indonesia, one of them in an animal husbandry, including in Kuantan Singingi Regency of Riau Province. In 2012 at Kuantan Singingi Regency there were 40.208 cattles and bufallos and 16,7% of them released for and disturbed the public. Because of much the livestock roamed, then out the regulation of Regent Kuantan Singingi Number 12th 2012 years about controling livestocks and rabies transmitting animals in 2012-2013.This research was used qualitative descriptive approach, technique of data collection is done by the informant in depth interview and documentation. The theory was used to discuss G.C. Edward III model theory.The fact of results obtained were follows : (1) the implementations of this rule is was merely socialization. (2) Relatively minimal funding be one of reason for the implementation of this rule does not run optimally including the absence of supporting infrastructure. (3) Existence of tradition or custom issues of indigenous people around the area who collide with the rule. The conclusion of this research that the policy makers ware less prepared for facilitating policies are made.Keywords: Policy Implementation, Government, animal Husbandry